An I/O interface for accessing fault data on the trains - Tan, Boon Kiat. (2009)
In Singapore Mass Rapid Transit (SMRT) , fault monitoring is a key part of corrective maintenance. The principle goal of this project is to develop an I/O interface to extract fault data from a fault Data Memory Card (DMC). The retrieval of fault data requires the use of an interface which is known as the transmitter.